1992
DOI: 10.1021/es00027a019
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of atrazine with Laurentian soil

Abstract: Ultrafiltration and. HPLC are applied to the study of binding of the neutral polar herbicide atrazine by a well-characterized Laurentian soil. This investigation exploits the results of our previous studies on the interaction of atrazine with fulvic acid and humic components extracted from this soil. The purpose of the study is to compare behavior of separate components to that of the soil assembly. These earlier studies established that a specific site complexation model, formally similar to a Langmuir isothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 19 publications
0
42
0
2
Order By: Relevance
“…Some models for the adsorption of organic species onto clays and other minerals assume that naturally present humic and fulvic acids coat the mineral surfaces [40,[50][51][52], and then contaminants interact with that organic coating. A common organic acid, acetic acid, becomes strongly bound to some mineral surfaces and forms soluble organo-metallic complexes with the minerals [53,54], but the rate of organic-clay reactions is relatively slow compared to the timescales of most experiments.…”
Section: Pah Resultsmentioning
confidence: 99%
“…Some models for the adsorption of organic species onto clays and other minerals assume that naturally present humic and fulvic acids coat the mineral surfaces [40,[50][51][52], and then contaminants interact with that organic coating. A common organic acid, acetic acid, becomes strongly bound to some mineral surfaces and forms soluble organo-metallic complexes with the minerals [53,54], but the rate of organic-clay reactions is relatively slow compared to the timescales of most experiments.…”
Section: Pah Resultsmentioning
confidence: 99%
“…Clinton Lake is a major source of drinking water for Lawrence, Kansas, and the Wakarusa River is the primary source for Clinton Lake Reservoir. The Laurentian soil fulvic acid (LSFA), isolated from the Laurentian area [16,17], was purchased from Fredriks Research Products. Even though this soil fulvic acid is not directly relevant to THM production in aquatic humic substances, it is important to test the analytical methods on a variety of humic structures.…”
Section: Methodsmentioning
confidence: 99%
“…Even though this soil fulvic acid is not directly relevant to THM production in aquatic humic substances, it is important to test the analytical methods on a variety of humic structures. Isolation and characterization of the SRFA, SRHA, WRHA, WRFA, CLFA, and LSFA are described in detail elsewhere [14,15,16,17].…”
Section: Methodsmentioning
confidence: 99%
“…Up to now, various studies on a wide range of pesticides (Wang et al 1992) have shown that their sorption on soils or organic matter depends on the pH. Except at pH>10, where a re-dissolution of lignocellulose occurs, surprisingly, it appeared that the pH does not influence the retention capacity of the solid for both isoproturon and dimetomorph.…”
Section: Adsorption Isothermsmentioning
confidence: 98%